Change in technology and equipment to simplify implementation of neutralization of oil-contaminated soil by the method of reagent capsulation in winter conditions - V. V. Merkulov; Yu. V. Kalinin; L. O. Shtripling (Омский научный вестник)
The article discusses some features of the implementation of the reagent encapsulation method in winter conditions. When preparing the next batch of oil-contaminated soil in a mixture with snow, a sufficient amount of water is formed, which can be used in the technological process, in this regard, it is proposed to make a change in the design of the installation. Since the presence of water in the contaminated soil prevents the mixing process with lime, it is proposed to change the traditional technology of reagent encapsulation. During the experiment, the possibility of implementing the encapsulation process using the modified technology is determined.